MOTIVASI BERPRESTASI ATLET BOLA VOLI PUTRA SMP NEGERI 15 PEKANBARU - Ifri Setiawan; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research objectives to be achieved in this study are: To find a picture of the achievement motivation of the athlete men's volleyball SMP 15 Pekanbaru. This research is descriptive, the research methods used to find the widest possible knowledge of the research object that is intended to gather information about the status of a variable or theme, symptoms or circumstances that exist, which is the state according to what their symptoms at the time of the study. The population in this study were male athlete who participated in the volleyball SMP 15 Pekanbaru much as 12 In this study, the sampling technique using total sampling technique, or all the athlete men's volleyball SMP 15 Pekanbaru many as 12 athletes. In this analysis of all the data that has been collected, processed and analyzed in accordance with the manner and conditions stated in the chapter preceding, the following will be analyzed the problems encountered in this study sequentially on "motivation of the athlete's performance volleyball SMP 15 Pekanbaru , Based on the results of achievement motivation volleyball athletes SMP 15 Pekanbaru son of five indicators that is equal to 84.29%. If we compare with the percentage descriptive analysis criteria can be classified Neither ie with a range of 76% -100%.Keywords:, motivation and achivement